Education and Health in Sub-Saharan Africa : A Review of Sector-Wide Approaches (the international bank for reconstruction and development, 2001)
This report reviews the experience to date of the Africa region in the Bank with this approach: it summarizes the lessons learned, identifies the strengths and weaknesses of this approach, and provides guidance and advice to operation staff in the Bank as well as partner agencies and governments who will be involved in sector-wide approaches in the year to come.